Morphometric and histological features of the testicles of cultured male broodstock African Catfish (Clarias gariepinus) at different ages - NWABUISI, OKOYE CHIDOZIE; UDOUMOH, ANIETIE FRANCIS; OMUBOBA, DAN-JUMBO SUSAN; UCHENNA, EZE UKAMAKA; CHUKWUEMEKA, OZOKOYE ANTHONY; HULDA, UGWU ONYINYECHI (Journal of the Hellenic Veterinary Medical Society, 2018)
Testicular tissues obtained from 25 apparently healthy broodstock African Catfish (Clarias gariepinus) of 6, 8, 9, 10 and 12 months old were used to investigate the morphological adaptations of the testicles suitable for reproductive exercises. The result showed that the mean gonadosomatic indices of the pooled testicles of the catfish increased linearly from 0.30 ± 0.02, 0.34 ± 0.01, 0.45 ± 0.09 at 6, 8, and 9 months of age respectively and peaked at 12 months with a GSI value of 0.61±0.13. Moreover, the epithelial height of the seminiferous tubules of 9 month old catfish was significantly (P<0.05) higher than the epithelial heights of the 6, 8, 10 and 12 month old fish. The luminal diameters of the seminiferous tubules of the testicles of 10 and 12 months old catfish were significantly (P<0.05) higher than the luminal diameters of the 6, 8 and 9 months old fish. The encapsulated testicles of the catfish exhibited seminiferous lobules which contained spermatogenic cells in cysts. However, at 10 months, there were partial distortion of the cystic distribution of the spermatogenic cells and occasional loss of the germinal epithelium while evidences of necrosis of some of the cells of the seminiferous epithelium were recorded in the testicles of 12 months old fish. Finally, the present study has provided morphological evidences that the use of gonadosomatic indices alone in the determination of the reproductive state of a fish population may give an erroneous picture and that the 8 and 9 months old broodstock African Catfish (Clarias gariepinus) may be most suitable for breeding exercises.